Effectiveness of a mobile cooperation intervention during the clinical practicum of nursing students: a parallel group randomized controlled trial protocol - Camilla Strandell-Laine; Mikko Saarikoski; Eliisa Löyttyniemi; Leena Salminen; Reima Suomi; Helena Leino-Kilpi (Wiley, 2022)
Aim
The aim of this study was to describe a study protocol for a study evaluating the effectiveness of a mobile cooperation intervention to improve students’ competence level, self-efficacy in clinical performance and satisfaction with the clinical learning environment.
Background
Nursing student–nurse teacher cooperation during the clinical practicum has a vital role in promoting the learning of students. Despite an increasing interest in using mobile technologies to improve the clinical practicum of students, there is limited robust evidence regarding their effectiveness.
Design
A multicentre, parallel group, randomized, controlled, pragmatic, superiority trial.
Methods
Second-year pre-registration nursing students who are beginning a clinical practicum will be recruited from one university of applied sciences. Eligible students will be randomly allocated to either a control group (engaging in standard cooperation) or an intervention group (engaging in mobile cooperation) for the 5-week the clinical practicum. The complex mobile cooperation intervention comprises of a mobile application-assisted, nursing student–nurse teacher cooperation and a training in the functions of the mobile application. The primary outcome is competence. The secondary outcomes include self-efficacy in clinical performance and satisfaction with the clinical learning environment. Moreover, a process evaluation will be undertaken. The ethical approval for this study was obtained in December 2014 and the study received funding in 2015.
Discussion
The results of this study will provide robust evidence on mobile cooperation during the clinical practicum, a research topic that has not been consistently studied to date.